2012
DOI: 10.1002/jat.2716
|View full text |Cite
|
Sign up to set email alerts
|

3‐(3,4‐Dihydroxyphenyl)adenine, a urinary DNA adduct formed in mice exposed to high concentrations of benzene

Abstract: Metabolism of benzene, an important environmental and industrial carcinogen, produces three electrophilic intermediates, namely, benzene oxide and 1,2- and 1,4-benzoquinone, capable of reacting with the DNA. Numerous DNA adducts formed by these metabolites in vitro have been reported in the literature, but only one of them was hitherto identified in vivo. In a search for urinary DNA adducts, specific LC-ESI-MS methods have been developed for the determination in urine of six nucleobase adducts, namely, 7-pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Collectively, these results do not support the overall hypothesis that benzene oxide-DNA adduct formation is important in carcinogenesis by benzene in B6C3F 1 mice, although it is recognized that adducts from other benzene metabolites such as o-or p-benzoquinone could still be involved. An adduct of obenzoquinone, 3-(3,4-dihydroxyphenyl)adenine, has been detected in the urine of mice exposed to benzene [18].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results do not support the overall hypothesis that benzene oxide-DNA adduct formation is important in carcinogenesis by benzene in B6C3F 1 mice, although it is recognized that adducts from other benzene metabolites such as o-or p-benzoquinone could still be involved. An adduct of obenzoquinone, 3-(3,4-dihydroxyphenyl)adenine, has been detected in the urine of mice exposed to benzene [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the results of comet assay showed that severe DNA damage occurred in G6PD inhibition cells compared with that in control cells at 20 μ mol/L BQ treatment, suggesting that BQ-induced inhibition of G6PD could increase DNA damage in K562 cell line. In addition to inducing ROS generation, BQ could form DNA-adducts that also cause DNA damage [ 28 ]. The present study found that DNA damage in control cells increased at 20 μ mol/L, in accordance with ROS level increasing at 20 μ mol/L BQ.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results do not support the overall hypothesis that benzene oxide-DNA adduct formation is important in carcinogenesis by benzene in B6C3F 1 mice, although it is recognized that adducts from other benzene metabolites such as o - or p -benzoquinone could still be involved. An adduct of o -benzoquinone, 3-(3,4-dihydroxyphenyl)adenine, has been detected in the urine of mice exposed to benzene [18]. …”
Section: Discussionmentioning
confidence: 99%